STUDY OF WORKLOAD AND EMPLOYEE COMPETENCE TOWARDS EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE - Nafiudin; Nurjanah, Siti; Tjalla, Awaluddin; Suparno, Suparno; Febriantina, Susan; Andari, Andari; Fujianti, Aini; Fauzan, Alfa; Sanjaya, Brata; Suprayogi, Wahyu (Fakultas Ekonomi, Universitas Negeri Jakarta, 2023)
Employee performance that is not as expected has an impact on the overall performance of the organization, so the focus of this study is to examine the influence of workload, competence on employee performance through organizational commitment studies on employees of PT Hitachi Metals Indonesia Cilegon with a total sample of 100 employees in the Quality Control Division, the data collection technique used is the distribution of questionnaires with a Likert scale as a rating scale, In this study, the hypothesis is tested using path analysis with SPSS and the Sobel Test, and the results show that workload has a positive effect on commitment and performance, and competence has a positive effect on employee commitment and performance. While organizational commitment can mediate between workload and performance, as well as competence and performance.